Gender Representation in Madurese Folktales: A Critical Discourse Analysis - Faridatuz Zulfa; Qadrina Lailyn Amrullah; Ijabah, Nur (Acitya: Journal of Teaching and Education, 2025)
This study explores gender representation in Madurese folktales using Norman Fairclough's Critical Discourse Analysis (CDA). By analyzing two selected folktales, The Origin of the Madurese People and Menak Sanaya, the research examines textual, discursive, and sociocultural dimensions to understand how gender roles are portrayed and their implications on societal perceptions. The findings reveal a recurring pattern of patriarchal ideologies where male characters are depicted as dominant, protective, and decision-makers. In contrast, female characters are relegated to subordinate roles, often portrayed as passive and reliant on male intervention. These representations reflect traditional Madurese societal values and contribute to the reinforcement of gender hierarchies. The study highlights how narratives serve as tools for intergenerational transmission of cultural norms, shaping collective consciousness and perpetuating gender stereotypes. Insights from this research emphasize the need for critical engagement with cultural narratives to foster discussions on gender equality.